2018
DOI: 10.1186/s12891-018-2215-3
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin versus other anti-thrombotic agents for prevention of venous thromboembolic events after total hip or total knee replacement surgery: a systematic review and meta-analysis

Abstract: BackgroundVenous thromboembolism (VTE) is an important complication following total hip replacement (THR) and total knee replacement (TKR) surgeries. Aim of this study was to comprehensively compare the clinical outcomes of low-molecular-weight heparin (LMWH) with other anticoagulants in patients who underwent TKR or THR surgery.MethodsMedline, Cochrane, EMBASE, and Google Scholar databases were searched for eligible randomized controlled studies (RCTs) published before June 30, 2017. Meta-analyses of odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…In our study, the incidence of proximal and mixed thrombus was 5.9%, in range of reported figures of 3.6-8.8% [5,10,13]. The studies have demonstrated that 4-11% of the proximal thrombus would progress to lead to pulmonary embolism [14], which further highlighted the importance of screening of DVT upon at admission.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, the incidence of proximal and mixed thrombus was 5.9%, in range of reported figures of 3.6-8.8% [5,10,13]. The studies have demonstrated that 4-11% of the proximal thrombus would progress to lead to pulmonary embolism [14], which further highlighted the importance of screening of DVT upon at admission.…”
Section: Discussionsupporting
confidence: 67%
“…We identified 9 systematic reviews addressing this research question. [157][158][159][160][161][162][163][164][165] We identified 14 studies [166][167][168][169][170][171][172][173][174][175][176][177][178][179] in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context. Our systematic search of RCTs identified 6 additional studies [180][181][182][183][184][185] not included in previous systematic reviews that fulfilled the inclusion criteria.…”
Section: Recommendationmentioning
confidence: 99%
“…The current guidelines for thromboprophylaxis recommend the use of vitamin K antagonists (e.g., warfarin), low-molecular-weight heparins (LMW heparin) or aspirin [ 28 – 30 ]. Polish experts and non-experts agreed on the use of LMW heparin, following the recommendations regarding venous thromboembolism prevention in orthopaedic surgery and traumatology developed by Polish orthopaedic surgery experts under the auspices of the National Consultant for Orthopaedic Surgery and Traumatology and the chairman of the Polish Society for Orthopaedic Surgery and Traumatology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%